Screening for abiotic stress resistance in root and tuber crops: IITA research guide, No. 68 - Ekanayake, I.J. (1998)
The main abiotic stress factors affecting root and tuber crops in sub-Saharan Africa are drought, waterlogging, temperature extremes, solar radiation extremes, and nutrient imbalances. To reduce the effects of abiotic stress, researchers breed crops that have high levels of resistance to the relevant stress factors. Researchers identify traits that confer resistance to stress factors. Genotypes with desirable traits are selected by screening, and used to breed populations with improved resistance.